Dynamic model to analyze pedestrian traffic policies in bogota (2014)
Pedestrian systems are increasingly becoming important for transportation planning in cities, however, approaches are meant for microscopic analysis and representation, thus do not seem to be adequate for decision making at this specific strategic level, because of their feedback relationships between different levels, which cannot be easily represented with these approaches. This paper presents a prototype for analysis at strategic level of pedestrian systems, by making use of industrial dynamics. This approach allows to represent the relations of these feedback systems, through the use of both quantitative and qualitative, to analyze the responses of the system in the long run. It is concluded that the proposed prototype allows to be a support for the strategic decisions of these systems; allows analysis related to investment in education and regulation of deaths and injuries as well as their impact on the accident and the social cost.